ANALISIS GAS TERLARUT PADA MINYAK ISOLASI TRANSFORMATOR TENAGA AKIBAT PEMBEBANAN DAN PENUAAN - Hermawan Hermawan; Abdul Syakur; Irwan Iryanto (TEKNIK, 2011)
The lifetime of transformers and its equipments are highly dependent on the quality of insulation system.Insulation is one important component in a transformer because generally, insulations used liquid and solidinsulation in accordance with its function as an insulating material and cooling media. At the time there usedtransformer oil aging and damage caused by several things such as impurities, water content, dissolved gases(Dissolved Gas Analysis-DGA), acidity and heating the oil. Transformers loading will cause a decrease in thequality of the transformers insulation system that resulted in the decreasing age of insulating oil.This paper explained the influence of aging on the rate of degradation of Dissolved Gases of power transformersinsulating oil. This research was conducted using sample data loading and maintenance of transformers byobtained directly with investigations into the transformers which is operating. There are three method todetermine quality of oil transformer i.e. Total Combustible Gases (TCG), Roger Ratio, Key Gas and DuvalTriangle Methods.Based on analysis result by using samples from a variety of loading conditions of the transformers with differentlevels we can conclude the quality and worthiness of insulation oil and the estimated the effective remaining lifeof transformers insulation system.